2022
DOI: 10.1108/rpj-01-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fused filament fabrication parameters on the manufacturing of 316L stainless-steel components: geometric and mechanical properties

Abstract: Purpose The extrusion-based additive manufacturing method followed by debinding and sintering steps can produce metal parts efficiently at a relatively low cost and material wastage. In this study, 316L stainless-steel metal filled filaments were used to print metal parts using the extrusion-based fused filament fabrication (FFF) approach. The purpose of this study is to assess the effects of common FFF printing parameters on the geometric and mechanical performance of FFF manufactured 316L stainless-steel com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Whereas, PS showed little or no influence on shrinkage rate within this experimental design (which corresponds to a subset of the broader range of acceptable set of parameters). While it is evident from the results presented above that MEX process parameters indeed influence the shrinkage properties of Steel 316L parts, interestingly, Caminero et al (2022) found that build orientation, LH and PS had no significant effect on shrinkage rate, although, they found nozzle diameter to influence shrinkage behaviour. Quarto et al (2021), on the other hand, found manufacturing parameters to influence each axis differently, with PS topping the list, followed by LH and nozzle temperature.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Whereas, PS showed little or no influence on shrinkage rate within this experimental design (which corresponds to a subset of the broader range of acceptable set of parameters). While it is evident from the results presented above that MEX process parameters indeed influence the shrinkage properties of Steel 316L parts, interestingly, Caminero et al (2022) found that build orientation, LH and PS had no significant effect on shrinkage rate, although, they found nozzle diameter to influence shrinkage behaviour. Quarto et al (2021), on the other hand, found manufacturing parameters to influence each axis differently, with PS topping the list, followed by LH and nozzle temperature.…”
Section: Resultsmentioning
confidence: 89%
“…From the ANOVA statistical results, LH and RA were found to be the most statistically significant manufacturing parameters influencing the shrinkage behaviour of the MEX Ultrafuse Steel 316L specimens, while PS was found to have little or no influence on the shrinkage behaviour (within the experimental design). Quarto et al (2021) similarly established the influence of MEX parameters on subsequent shrinkage behaviour of Steel 316L specimens, while Caminero et al (2022) found varying manufacturing parameters to have a negligible influence on shrinkage rate.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For this reason, 316L is one of the most researched materials in the field of FFFm. Numerous studies on filament-based fabrication of steel have investigated the print-porosity and its influence on the mechanical anisotropy [4,[11][12][13][14][15], surface roughness [16,17], or fatigue [18]. The sintering process has fundamental effect on the final microstructure and the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%